Use of the target language in the French language classroom: co-operative teaching as an aid to implementation - Franklin, Carole E. M. (University of Edinburgh, 1990)
Findings of empirical studies into the importance of input in foreign language learning suggest that, to provide sufficient communicative foreign language input in the context of school language classrooms, learners must be taught through the medium of the target language. Research shows that teachers who share a mother tongue with their learners often find it difficult to avoid breaking into the mother tongue to deal with classroom management but, when they do so, they not only restrict the amount of meaningful input to which the learners are exposed, but also risk slowing down the acquisition process. New data (gathered by means of two postal surveys during session 1987-88) show that non-native secondary school teachers of French in the Strathclyde Region of Scotland identify a hierarchy of difficulty among classroom management tasks ranging from tasks which are moderately simple to conduct in the foreign language (such as classroom organisation) to tasks which are extremely difficult to perform in the target language (such as discussing grammar). Further analysis of the survey data reveals that teachers who have a positive attitude towards the use of the target language as the medium of instruction have certain defining characteristics, the most important of which relate to enthusiasm for the foreign language. In an attempt to find a way of helping teachers to teach through the medium of the target language, this thesis investigates claims made by practising teachers that teaching co-operatively with a second fluent target language speaker helps them maintain the use of French as the medium of instruction. Using survey and observational data, the thesis concludes that co-operative teaching can both increase the quantity, and improve the quality of foreign language input to which learners are exposed. Furthermore, co-operative teaching is a valuable tool in the organisation and implementation of communicative language teaching methodology. The thesis is in two parts: • Part one provides the theoretical basis of the thesis, and describes the research context and design. • Part two analyses the findings of the mail administered surveys and of the small-scale observation study, and draws conclusions based on these findings. # # # NOTE: In this thesis, while it is recognised that learners and teachers are just as likely to be female as male, for ease of expression they are treated as "impersonal masculine" throughout.
The use of the target language in the French language classroom: co-operative teaching as an aid to implementation
Keywords: Education; Linguistics